(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
Missed abortion remains one of the leading causes of early reproductive loss and continues to be an important medical and social problem in modern obstetric and gynecological practice. According to the World Health Organization, a significant proportion of spontaneous pregnancy losses in early gestation is associated with impaired implantation and early embryogenesis. In recent years, chronic endometritis has attracted considerable attention as one of the major pathogenetic factors contributing to missed abortion. Persistent inflammatory changes in the endometrium are accompanied by impaired endometrial receptivity, microcirculatory disorders, cytokine imbalance, hormonal dysregulation, and disturbances in the microbiological status of the reproductive tract. Chronic inflammation negatively affects trophoblast invasion, chorionic development, and proper implantation of the fertilized ovum, significantly increasing the risk of recurrent reproductive failure. Therefore, the development of effective pregravid rehabilitation methods aimed at restoring the functional state of the endometrium is of great clinical importance.